Republic of the Marshall Islands : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2011)
The economy of the Republic of the Marshall Islands has experienced a strong recovery with a 5.2 percent growth in 2010 following strong improvement in the fisheries sector and a moderate recovery in exports. The financial sector remained focused on consumer lending and contributed little to overall economic growth. Although the financial sector remained profitable, much of the rapid growth in credit has been in consumer loans. The authorities are monitoring high levels of household debt and intend to begin work on strengthening the regulatory framework.